Menakar Efektivitas Mediasi Pasca Regulasi PERMA Nomor 1 Tahun 2016 (Studi Analisis Pengadilan Agama Pamekasan) - Rohman, Moh. Mujibur (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The divorce rate in Pamekasan Kapaten is increasing from year to year, where from 2017 to mid-2020 there was a significant increase in the divorce rate. The government is always trying to try various ways to stem the increase in divorce rates, one of these efforts is mediation as a form of proactive action by the courts in reconciling citizens who are in dispute. The focus of the research is on: 1) How is the conceptualization of mediation in both Islam and Positive law?, 2) What is the significance of changes in PERMA from 2003, 2008 and 2016? and 3) How effective is mediation at the Pamekasan Religious Court?. This research is field research (empirical) using a qualitative approach and does not exclude library data (library research). The aim of this research is to examine the effectiveness of mediation in reducing the divorce rate within the scope of the Pamekasan Religious Court after the latest regulations, namely PERMA No. 1 of 2016 concerning Mediation Procedures in Court. The results of this research show that there are things that are less effective in implementing mediation at the Pamekasan Religious Courts related to things that are entrenched in society, namely always prioritizing egoism in resolving problems, especially Pamekasan culture with its Madurese characteristics and the lack of public understanding of mediation at the Religious Courts.